Improvement of the Sound Absorption Performance of Sandwich Panel Using Inhomogeneous Micro Perforations - Laly, Zacharie; Mechefske, Christopher; Ghinet, Sebastian; Kone, Charly T.; Atalla, Noureddine; Ashrafi, Behnam (Canadian Acoustics, 2024)
Sandwich structures are widely used in several fields because of their mechanical performance with low weight. In this paper, a sandwich panel made of a core and a top and a back panel is investigated using the finite element method. The core consists of 33 hexagonal cells and each cell is connected to a micro-perforation. To improve the sound absorption, inhomogeneous micro-perforations are considered within the top panel. It is shown that with homogenous micro-perforations made of the same diameter, the sound absorption coefficient presents only one resonant peak. When 2, 3 and 6 different sets of micro-perforation diameters are considered, the sound absorption coefficient presents respectively 2, 3 and 6 resonance peaks where the surface impedance is close to that of the air. When each micro-perforation diameter is different resulting in inhomogeneous distribution of micro-perforations within the top panel, the sound absorption frequency band is widened and the absorption coefficient value increases while without micro-perforations the absorption coefficient of the sandwich panel is zero over the entire frequency range. The studied structure can offer high mechanical stiffness and good sound absorption performance.